AI in Fashion Industry - Banerjee, Satya; Mohapatra, Sanjay; Bharati, M. (Emerald points., 2022)
AI in Fashion Industrydiscusses recent developments in fashion forecasting, developing a 'framework of AI-based fashion forecasting' and validates the framework with a qualitative case study of the world's first fashion intelligence company based in Bengaluru, India.- Resumé vydavatel